Maximal heart rate for swimmers - Olstad, B. H.; Bjørlykke, V.; Schäfer Olstad, D, (Sports, 2019)
The main purpose of this study was to identify whether a different protocol to achieve maximal heart rate should be used in sprinters when compared to middle-distance swimmers. As incorporating running training into swim training is gaining increased popularity, a secondary aim was to determine the difference in maximal heart rate between front crawl swimming and running among elite swimmers. Twelve elite swimmers (4 female and 8 male, 7 sprinters and 5 middle-distance, age 18.8 years and body mass index 22.9 kg/m2) swam three different maximal heart rate protocols using a 50 m, 100 m and 200 m step-test protocol followed by a maximal heart rate test in running. There were no differences in maximal heart rate between sprinters and middle-distance swimmers in each of the swimming protocols or between land and water (all p = 0.05). There were no significant differences in maximal heart rate beats-per-minute (bpm) between the 200 m (mean ± SD; 192.0 ± 6.9 bpm), 100 m (190.8 ± 8.3 bpm) or 50 m protocol (191.9 ± 8.4 bpm). Maximal heart rate was 6.7 ± 5.3 bpm lower for swimming compared to running (199.9 ± 8.9 bpm for running; p = 0.015). We conclude that all reported step-test protocols were suitable for achieving maximal heart rate during front crawl swimming and suggest that no separate protocol is needed for swimmers specialized on sprint or middle-distance. Further, we suggest conducting sport-specific maximal heart rate tests for different sports that are targeted to improve the aerobic capacity among the elite swimmers of today.